2009
DOI: 10.1002/rcm.4264
|View full text |Cite
|
Sign up to set email alerts
|

Increasing high‐throughput Discovery bioanalysis using automated selected reaction monitoring compound optimization, ultra‐high‐pressure liquid chromatography, and single‐step sample preparation workflows

Abstract: QuickQuan is an integrated software package for Thermo Scientific triple quadrupole mass spectrometers that allows users to automate routine operations ranging from method development to data processing. QuickQuan automated optimization of compound-selected reaction monitoring (SRM) transitions by evaluating both positive and negative polarities during an infusion. Whichever mode produces the most intense Q1 scan is then carried to product ion spectra. QuickQuan then writes these SRM methods to a shared networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…[28] Smalley et al suggested the requirement of a minimum of 10 data points across a chromatographic peak for adequate bioanalytical quantitation with UPLC-MS/MS in a discovery setting. [29] In our current method, the RF-MS/MS peaks for both digoxin and the internal standard were approximately 2 s wide at base. By using an SRM dwell time of 70 ms each for digoxin and internal standard, we ensured that more than 13 data points were obtained across the peak to achieve reliable quantitation, as demonstrated by the accurate and precise data presented in Tables 1-4 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[28] Smalley et al suggested the requirement of a minimum of 10 data points across a chromatographic peak for adequate bioanalytical quantitation with UPLC-MS/MS in a discovery setting. [29] In our current method, the RF-MS/MS peaks for both digoxin and the internal standard were approximately 2 s wide at base. By using an SRM dwell time of 70 ms each for digoxin and internal standard, we ensured that more than 13 data points were obtained across the peak to achieve reliable quantitation, as demonstrated by the accurate and precise data presented in Tables 1-4 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…21) The flow injection analysis was conducted using a standard solution of fexofenadine and the Automaton ® software for automated optimization of SRM to obtain the precursor and product ions of fexofenadine. 26,27) The precursor ion of fexofenadine was m/z 502 of protonated ions [M+H] + . The product ion at m/z 466 represented the highest ion intensity in the product ions from m/z 502; moreover, the product ion at m/z 171 was detected (Fig.…”
Section: Uhplc-ms/ms Conditionsmentioning
confidence: 99%
“…The market entry of the techniques of ultra‐high‐pressure liquid chromatography (UHPLC or UPLC) has managed to reduce the time analysis and the effectiveness of the separations. Thus, methods have been developed for the determination of CIT and other compounds by UPLC‐MS‐MS with a total run time for all analyses of 1.2 min using BEH 1.7 micron particle C 18 columns (Smalley et al ., 2009). Similarly, using Q‐TOF mass analyzers, Nielsen et al .…”
Section: Liquid Chromatographymentioning
confidence: 99%